2003
DOI: 10.1080/0954012031000068380
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative assessments of HAART adherence of substance-abusing women

Abstract: This study was set up to examine factors affecting adherence to highly active antiretroviral therapy (HAART) by substance abusing women and to conduct a pilot study of a reminder device intervention. Three focus groups totaling 24 HIV-positive women developed priority lists of issues affecting adherence. Another group of 24 HIV-positive women received a timer-reminder with structured interviews on adherence at baseline and two monthly follow up intervals. Focus groups described key barriers to HAART adherence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 21 publications
(36 reference statements)
2
46
0
4
Order By: Relevance
“…28 "Forgetting" may be a proxy for psychological processes such as avoidance and denial. 59 Depression 5,60 and posttraumatic stress related to the HIV diagnosis, 61 other mental health problems, 56 and limited adherence-specific or global social support 56 may fuel this avoidance or otherwise make dose administration difficult if not impossible. Surely most caregivers want to their child to get this critical med-…”
Section: Said They Used No Strategiesmentioning
confidence: 99%
“…28 "Forgetting" may be a proxy for psychological processes such as avoidance and denial. 59 Depression 5,60 and posttraumatic stress related to the HIV diagnosis, 61 other mental health problems, 56 and limited adherence-specific or global social support 56 may fuel this avoidance or otherwise make dose administration difficult if not impossible. Surely most caregivers want to their child to get this critical med-…”
Section: Said They Used No Strategiesmentioning
confidence: 99%
“…For example, given that forgetting to take ART has been reported to be one of the most commonly stated adherence barriers, [12][13][14][15][16] many studies have examined the use of reminder devices in improving adherence. [17][18][19][20] However, most have not revealed clinically significant changes in adherence. Studies have reported other adherence barriers, including feeling depressed or overwhelmed, fear of disclosure, sleeping through a dose, substance use, regimen complexity, not having medication, change in daily routine, and not wanting to be reminded of HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that procrastination and being too distracted or busy can lead to low HAART adherence (Hill, Kendall, & Fernandez, 2003;Powell-Cope et al, 2003;Westerfelt, 2004). One may procrastinate or be too busy or distracted due to work and/ or because they are searching for money to buy daily needs, among other reasons.…”
Section: Procrastination and Being Too Distracted Or Busymentioning
confidence: 99%